Assessment of subsurface features and potential of groundwater delineation using 2-dimensional electrical resistivity imaging method - Norshidah, Yunus; Nordiana, Mohd Muztaza; Ismail, Ahmad Abir; Bashir, Yasir; Muhammad Taqiuddin, Zakaria; Farid Najmi, Rosli; Ahmad Aqil, Ahmad Aznan; Gnapragasan, Joseph; Putra Jaya, Ramadhansyah; Nazrin, Rahman; Mohamed, Mustapha Adejo; Terkimbi, Ayaaka Dalton; et al. (Penerbit UMT, 2025)
The application of geophysical methods is widely used for the assessment of subsurface geological features, including the determination of potential groundwater aquifers, understanding of stratigraphy sequences, and structural analysis. The demand for groundwater exploration is on the rise, encompassing needs for domestic, industrial, and agricultural purposes. However, unsuccessful groundwater exploration has occurred owing to a lack of comprehensive subsurface information. Groundwater, as an alternative water source, remains largely unexplored within the Penang Island. In relation to this, a thorough study on the geophysics and geology should be carried out. It is certainly not as simple as just digging a well to draw water. Current technologies widely used for groundwater exploration include geophysical methods, remote sensing, Geographic Information System (GIS), hydrogeological, and machine learning. Therefore, geophysical methods were applied to obtain subsurface information to determine and classify the materials using selected geophysical properties. Geophysical methods, particularly Electrical Resistivity Tomography (ERT) is a non-invasive technique that allows for accurate identification of aquifer boundaries, saturated zones, and is cost-effective. This research aims to assess the subsurface features and evaluate the delineation of potential groundwater zones using 2-D electrical resistivity imaging and serves as a preliminary guide for identifying suitable locations for groundwater exploration in Universiti Sains Malaysia, Penang Island, Malaysia. Eight resistivity survey lines (LR01-LR08) are conducted within the research area. The 2-D resistivity imaging survey was conducted using Pole-dipole array for LR02, LR03, LR04, LR06, LR07, and LR08 while Wenner Schlumberger array for LR01 and LR03 with 5 m minimum electrode spacing. The Wenner-Schlumberger array was chosen due to site constraints in placing the remote electrodes within the study area. The research area’s geology is characterised by an underlying igneous rock, featuring a centrally positioned granitic range that extends in a north-south direction, accompanied by lowlying elevations ranging between 5 metres and 20 metres above sea level. For this research, an automated multi-electrode resistivity meter, the ABEM Terrameter SAS 4000 system is employed. The resistivity values underwent an inversion process using RES2DINV software to generate the electrical resistivity topography model. The resistivity profiles are cross plotted using Surfer 8 and Sketchup software to obtain the overview of resistivity anomalies continuity between the resistivity profiles. The results showed the resistivity values ranged from 1 Ωm to 20,000 Ωm. Subsurface materials were categorised into four types based on their resistivity value ranges: Water-saturated zones (1 Ωm to 300 Ωm), weathered material (301 to 1,000 Ωm), weathered bedrock (1,001 to 4,500 Ωm), and fresh bedrock (> 5,000 Ωm). Several faults and anomalies are interpreted as potential watersaturated zones for groundwater drilling purposes. They are the continuation of watercontaining zones between LR02, LR05, and LR08 profiles. These zones are proposed as a suitable potential location for drilling for groundwater. This outcome could contribute to establishing a one-stop centre for hardrock groundwater resources and developing sustainable guidelines for their management in the granitic region of Malaysia.